2019
DOI: 10.1126/sciadv.aav2554
|View full text |Cite
|
Sign up to set email alerts
|

Influenza binds phosphorylated glycans from human lung

Abstract: A novel array of human lung glycans reveals influenza A virus binding to phosphorylated as well as sialylated N-glycans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 43 publications
4
80
0
1
Order By: Relevance
“…Indeed, studies utilising glycan arrays clearly demonstrate that in addition to SIA‐linkage, other glycan properties such as branch patterns, chain length and modifications (e.g., fucosylation and sulphation) also modulate IAV attachment (reviewed in Viswanathan et al, ). Recent examination of the N ‐glycome of the human lung confirmed the importance of sialylated glycans for the binding of mammalian and avian IAV strains, but this study also demonstrated binding to phosphorylated, nonsialylated glycans, possibly through interactions with the viral HA and/or NA (Byrd‐Leotis et al, ).…”
Section: Susceptibility Of Host Cells To Iav Infection: Host and Virasupporting
confidence: 57%
“…Indeed, studies utilising glycan arrays clearly demonstrate that in addition to SIA‐linkage, other glycan properties such as branch patterns, chain length and modifications (e.g., fucosylation and sulphation) also modulate IAV attachment (reviewed in Viswanathan et al, ). Recent examination of the N ‐glycome of the human lung confirmed the importance of sialylated glycans for the binding of mammalian and avian IAV strains, but this study also demonstrated binding to phosphorylated, nonsialylated glycans, possibly through interactions with the viral HA and/or NA (Byrd‐Leotis et al, ).…”
Section: Susceptibility Of Host Cells To Iav Infection: Host and Virasupporting
confidence: 57%
“…Moreover, due to its high fluorescence sensitivity and conjugation yield, AEAB is ideal for development of natural glycan microarrays or shotgun glycomics, whereby all types of glycans could be isolated from natural sources and be fluorescently-tagged, purified by multi-dimensional chromatography, quantified and eventually printed on glass slides to create natural glycan microarrays. With this approach, we developed a variety of sequence-defined and shotgun glycan microarrays, including a human milk glycan array, a microbial glycan microarray (MGM), sequence-defined and shotgun Schistosome glycan arrays, a pig lung N-glycan array and more recently, a sequence-defined NCFG array, a lectin QA/QC array and a human lung shotgun N-glycan array (Byrd-Leotis et al, 2019b).…”
Section: Development Of Fluorescent Bi-functional Linkermentioning
confidence: 99%
“…This led to the broad screening of various strains of influenza viruses, including these H3N2 strains that have progressively undergone "antigenic drift" in their head domains (Byrd-Leotis et al, 2019a) Surprisingly, the H3N2 drift strains almost completely lost their capacity in binding of canonical sialylated N-glycans on the sequence-defined N-glycan array (Byrd-Leotis et al, 2019a). Moreover, the discoveries with the pig lung glycan array opened the door to later studies with actual human lung tissue to search for endogenous receptors for influenza viruses (Byrd-Leotis et al, 2019b). Interestingly, it was discovered that many of the influenza viruses tested not only bound to sialylated structures, but also to phosphorylated glycans present in human lung tissue (Byrd-Leotis et al, 2019b).…”
Section: Discovery Of Natural Glycan Ligands Involved In Infection Anmentioning
confidence: 99%
See 2 more Smart Citations